Cantù syndrome: Report of a patient with a novel variant in KCNJ8 and revision of literature. Issue 6 (3rd March 2022) - Apuril Velgara, Erika Solansh; Mariani, Milena; Torella, Annalaura; Musacchia, Francesco; ,; Nigro, Vincenzo; Selicorni, Angelo
Abstract: Cantù syndrome (CS) is a rare multisystemic disorder, characterized by congenital hypertrichosis, macrocephaly, facial dysmorphisms, cardiomegaly, vascular, and skeletal anomalies. From the cognitive point of view, most of the patients show a mild speech delay and a few of them present intellectual disability and learning difficulties. To date, most CS‐reported cases are caused by heterozygous ABCC9 gene mutations. Only three patients with CS and heterozygous KCNJ8 gene variants have been reported. The authors here present the fourth case of CS with a variant in KCNJ8 in a 6‐month‐old baby. Diagnosis was reached through Trio‐Whole Exome analysis that revealed a de novo missense variant in KCNJ8 .